THE EXTENT OF INTERNAL AUDIT EFFICIENCY TO LIMIT THE PRACTICES OF IMMORAL ACCOUNTANT FROM THE POINT OF VIEW OF AUDITORS FOR PURCHASING MANAGEMENT IN BAGHDAD - Alghazali, M Hazim (International Journal of Supply Chain Management, 2019)
Purchasing is the basic link in the process of enterprise management and the first link of enterprise cost control. Effective purchasing cost control will not only help the enterprise to reduce costs, but also to improve competitiveness. The existence of ethical accounting practices was one of the reasons of deficiencies and difficulties in the field of internal auditing as a profession, in addition to the use of modern techniques and methods to address the shortcomings and difficulties encountered by the form of ethical accounting practices, a great challenge to the accounting profession and auditing through the practices, procedures and policies used by accountants. The exploratory nature of this study was adopted by the researcher on the developmental approach, in which the various information available in the books and courses were extracted and results reached on the application of internal auditing and ethical accounting practices. We have experience that can help protect economic unity and reduce ethical practices. In order to do so, the technology of the systems of expertise can be used in the face of inefficiencies and inefficiencies in the performance of internal audits. As an important part of enterprise internal control, internal audit plays an important role for enterprise management in supervision and evaluation. However, at present, related researches on the internal audit of purchasing cost control in decoration projects are lacking. The research is based on the main hypothesis that there is a relationship of correlation between the effectiveness of internal audit and the practices of the ethical accountant in purchasing management.